Politics and post-colonial theory : African inflections - Ahluwalia, D. P. S. (D. Pal S.) (Routledge, 2002)
This groundbreaking book makes sense of the complexities and dynamics of post-colonial politics, illustrating how post-colonial theory has marginalised a huge part of its constituency, namely Africa. Politics and Post-Colonial Theory traces how African identity has been constituted and reconstituted by examining issues such as: * negritude * the rise of nationalism * decolonisation. The book also questions how helpful post-colonial analysis can be in understanding the complexities which define institutions including: * the nation-state * civil society * human rights * citizenship. Politics and Post-colonial Theory bravely breaks down disciplinary boundaries. Its radical vision will be essential reading for all those engaged in Politics, post-colonial studies and African studies.